Widerstand: el valor de la resistencia política en Immanuel Kant - Lepe Carrión, Patricio (Nómadas. Critical Journal of Social and Juridical Science, 2011)
This article aims to show a new interpretation on the concept of Widerstand. Has historically been understood as a denial by the legal system, while the resistance would be an event in itself reprehensible, but has forgotten that for Kant, the modification of the pillars of the State or the transformation of its socio-political environment, is only possible through ethics (ie, a resistance 'enlightened') as a bridge is the shift from a personal morality (Doctrine of Virtue) to a political morality (Doctrine of Right) and from there, towards the construction of a unattainable, but hopeful perpetual peace.
Keywords: Widerstand; Aufklarung; Resistance; Enlightenment; Freedom